(untitled) (Althea Medical Journal, 2025)
Background: Stroke is a complex condition that often leads to physical impairment and psychological challenges. Psychological well-being plays a crucial role in improving the quality of life and overall recovery in post-stroke patients. This study aimed to identify factors linked to psychological well-being in non-haemorrhagic post-stroke patients. Methods: A cross-sectional study was conducted in November 2022, included patients with a confirmed diagnosis of non-hemorrhagic stroke at the K.R.M.T Wongsonegoro Hospital, Semarang, Indonesia. Participants were selected through purposive sampling. After obtaining informed consent, data on demographic characteristics, family welfare status, and psychological well-being were collected. Psychological well-being was assessed using a standardized questionnaire. Data were analyzed using SPSS version 26, and associations between variables were examined using the Spearman correlation test. Results: A total of 80 non-hemorrhagic post-stroke patients participated, with the majority aged over 65 years (53%). Most participants (58.8%) reported strong family support, and had moderate psychological well-being (76%). Both the level of education and the degree of family support were significantly related to psychological well-being (p=0.028). Conclusion: Education level and family support are related to psychological well-being in non-haemorrhagic post-stroke patients. These finding highlight the need for a holistic approach to stroke recovery that includes psychosocial support, therapeutic interventions, and family involvement. Addressing psychological aspects along with physical rehabilitation can improve mental well-being and optimize recovery outcomes.